Pengaruh Over Capacity Terhadap Tingkat kefokusan Pembelajaran di SDN Gili Barat Bangkalan: Penelitian - Isham Husain; Marsha Amelia Putri; Dimas Agung Saputro; Naila Dwi Maulidia; Hikmah, Mamlu'atul; Gandy Asmara; Ahmad Sudi Pratikno (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to determine the effect of over capacity conditions on the level of student learning focus at Elementary School of Gili Barat Bangkalan. This study uses a descriptive quantitative approach with data collection techniques in the form of a questionnaire distributed to 37 students. The results showed that the majority of students felt that the large number of classmates caused the learning atmosphere to become unconducive, difficult to concentrate, and disrupted interactions with teachers. In addition, teachers also experience difficulties in managing crowded classes and providing individualized attention to each student. Limited space and infrastructure also worsen learning conditions in the classroom. Based on these findings, it is recommended that schools and policy makers reorganize the number of students per class and improve the quality of learning facilities to create a more conducive and effective learning environment.